Ecological Studies of Epiphytic Diatom on Eucheuma denticulatum (Rhodophyta) thallus Cultivated in Horizontal Floating Cage - Ma’ruf Kasim; Ade Winesti; Wa Nurgayah; Abdul Muis Balubi; Wardha Jalil (Bogor Agricultural University, Indonesia, 2022)
Epiphytic diatoms are phytoplankton groups commonly attached to substrates such as macroalgae. This study analyzes the community structure and diversity of epiphyte diatoms attached to Eucheuma denticulatum cultivated using the horizontal floating cage method. Six thalli of E. denticulatum propagules were taken randomly from each station. The samples were analyzed and identified in the laboratory. The research results clarified that epiphytic diatom composition consisted of 3 classes, two orders, 38 genera, and 79 species. The three classes that have been found include class Coscinodiscophyceae (10 genera) with percentages ranging between 8-34%, class Fragillaryophyceae (12 genera) with percentages ranging between 34-46%, and class Bacillariophyceae (16 genera) with percentages ranging between 26-46%. The uniformity index was 0.8287-0.9286, which is considered relatively high. The dominance species index was 0.0644-0.2055, categorized as low. Fluctuations in water's physical and chemical factors have no significant effect on the growth of diatom epiphytes in the thallus of E. denticulatum.